Antiviral Properties of the Seed Extract of an Indian Medicinal Plant, Pongamia Pinnata, Linn., Against Herpes Simplex Viruses: In-Vitro Studies on Vero Cells - Elanchezhiyan, M.; Rajarajan, S.; Rajendran, P.; Subramanian, S.; Thyagarajan, S. P. (Journal of Medical Microbiology, 1993)
Summary Pongamia pinnata, Linn., an Indian medicinal plant used in the Ayurvedha and Siddha traditional medicine systems, for treatment of clinical lesions of skin and genitalia, was evaluated for antiviral properties against herpes simplex virus type-1 (HSV-1) and type 2 (HSV-2) by in-vitro studies in Vero cells. A crude aqueous seed extract of P. pinnata completely inhibited the growth of HSV-1 and HSV-2 at concentrations of 1 and 20 mg/ml (w/v), respectively, as shown by complete absence of cytopathic effect.